Propensity-Matched Comparison of 90-Day Complications in Robotic-Assisted Versus Non-Robotic Assisted Lumbar Fusion. Issue 3 (1st February 2022) - Yu, Charles C.; Carreon, Leah Y.; Glassman, Steven D.; Brown, Morgan E.; Daniels, Christy L.; Polly, David W.; Gum, Jeffrey L.
Abstract : Study Design: Retrospective single center propensity-matched observational cohort study that included patients who underwent 1- to 3-level lumbar fusion surgery for degenerative conditions. Objective: To compare 90-day complication rates between robotic-assisted and non-robotic-assisted lumbar spinal fusions in propensity-matched cohorts. Summary of Background Data: A recent administrative database (PearlDiver) study reported increased 30-day complications with the utilization of robotic-assisted enabling technology. Methods: Of 146 robotic-assisted cases that met inclusion criteria, 114 were successfully propensity matched to 114 patients from 214 cases who had 1 to 3 level lumbar fusion without robotic assistance based on age, sex, body mass index, smoking status, American Society of Anesthesiologist grade, number of surgical levels, primary versus revision, and surgical approach (posterior-only or anterior-posterior). We excluded tumor, trauma, infection, or deformity cases. Outcomes included surgical and medical (major/minor) complications at intraoperative, immediately postoperative, 30- and 90-day postoperative intervals, including reoperations, and readmissions within 90 days. Results: All cause intraoperative complication rates were similar between non-robotic-assisted (5.3%) and robotic-assisted groups (10.5%, P  = 0.366). Immediate postoperative medical complication rate was also similar between non-robotic-assisted (6.1%) and robotic-assisted groups (1.8%, P  = 0.089). Thirty-day complication rates, 90-day complication rates, reoperation rates, and readmission rates showed no difference between non-robotic-assisted and robotic-assisted groups. There was no difference between return to OR for infection between the cohorts (non-robotic-assisted: 6 [5%] vs. robotic-assisted: 1 [0.8%], P  = 0.119). There was however improved length of stay (LOS) in the robotic-assisted group compared with non-robotic-assisted group (2.5 vs. 3.17 days, P  = 0.018). Conclusion: In propensity-matched cohorts, patients undergoing 1- to 3-level robotic-assisted posterior lumbar fusion for degenerative conditions did not have increased 90-day complication rate, and had a shorter length of stay compared with non-robotic-assisted patients. There findings differ from a prior administrative database study as the robotic-assisted group in the current study had 0% return to OR for malpositioned screws and 0.8% return to OR for infection. Level of Evidence: 2 Abstract : Robotic-assisted surgery results in improved pedicle screw accuracy, but its complication profile is debated. This retrospective propensity-matched cohort compares 90-day complication rates between robotic-assisted and non-robotic-assisted lumbar spine fusions. Not only is it safe, robotic-assisted surgery was associated with shorter length of stay compared with non-robotic-assisted surgery.